Development of a Registry for Down Syndrome in the Gulf Area of the Middle East - Corder, Jennifer (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
Systems for organizing specific data about large groups of people have been in existence for many years; their structures depend greatly on their purposes and goals. This paper describes the creation of a registry and database detailing demographics and co-occurring conditions of a population with Down syndrome living in the United Arab Emirates. The Gulf Down Syndrome Registry-Abu Dhabi seeks to describe the population’s demographics and associated co-occurring conditions, bringing attention to their unique needs through description of findings.
Keywords: Down syndrome